Student plagiarism in an online world problems and solutions - Roberts, Tim S., 1955- (Information Science Reference, 2008)
"This book describes the legal and ethical issues surrounding plagiarism, the tools and techniques available to combat the spreading of this problem, and real-life situational examples to further the understanding of the scholars, practitioners, educators, and instructional designers who will find this book an invaluable resource"--Provided by publisher.